Natural Resources Management - Mohan, Prasad C. (World Bank, Washington, DC, 2012)
Participatory community-based Natural Resources Management (NRM) Projects have been implemented over the last 5-6 years in Benin, Burkina Faso, Mali, and Niger with the support of France, Germany, Norway, the United States, and the World Bank's International Development Association facility. Furthermore, pilot operation concentrating on specific NRM issues are underway in Chad (pastoral perimeters) and Guinea (land tenure securement). Since 70 to 90 percent of the land in these countries is collectively owned, such projects are in fact trying to reinforce common property management systems, with the dual objective of alleviating poverty and improving the management of (crop) land, water, pasture, and forest resources. This Note summarizes the impact of NRM on the ground, presents the lessons learned, and provides a list of key documents on NRM.